(3Gdbhd GdSOjO hGdfeW GdLOjO aj hLhH QSe GdEeGe hGdJLhjOs - (3eMeO Hf QShd GdMSjfj GdHQRfLjs
(3ChdgG (B:s
(3GdMeO ddg GdPi HcTaI JfcTa GdeYVdGJ hHYO abO SCdJ ZjQ eQI Yf eSCdJjf GNJHW ajgG GdfGS hGNJdW ajgG GdHjGf hgj cJGHI GdeUMai dG Ydi QSe GdGeGe s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg (B: (3SejJ HPdc dLQjGf GdfaS eYgG jgeS hHYVgG CVYa aGdUGO hGdNGA Cbhi ef ZjQgeG dGf ai GdUGO CWHGbkG jLQi HHYV s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B249s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdbQGAGJ hGdJLhjOs